Analysis of the Role of Customer Satisfaction Mediation and Customer Value on the Influence of Service Quality on the Revisit Intention of BPJS Health Patients in the Inpatient Facility of Mitra Siaga Tegal Hospital - Rohmatullah, Rohmatullah; Hari Susanta Nugraha; Andi Wijayanto (International Journal of Economics, Business and Innovation Research, 2025)
Demands for improved quality of healthcare services in Indonesia, coupled with an increase in the number of public complaints, have raised public expectations of hospitals offering quality services, adequate facilities, and affordable costs. As a result, every hospital service must continuously strive to meet these expectations. This study aims to analyse the mediating role of customer satisfaction and customer value on the effect of service quality on the revisit intention of BPJS Kesehatan patients at the Inpatient Facility of Mitra Siaga Hospital in Tegal. The research method was conducted using a survey design through the distribution of questionnaires to inpatients who are BPJS Kesehatan participants. Data analysis was performed using SmartPLS. The results showed that service quality had a positive and significant effect on customer satisfaction and customer value, but did not have a direct effect on revisit intention. Customer satisfaction had a positive and significant effect on customer value and revisit intention, while customer value also had a positive and significant effect on revisit intention. Furthermore, it was found that Customer Satisfaction and Customer Value significantly mediate the effect of Service Quality on Revisit Intention. The results of this study confirm that the success of hospital management in improving service quality, satisfaction, and customer value will have an impact on the intention of BPJS Kesehatan patients to revisit the hospital. Management must implement patient-oriented strategies, strengthen a culture of excellent service, and integrate effective service systems to maintain the sustainability and competitiveness of the hospital. This study contributes both theoretically and practically by demonstrating that quality service will increase customer satisfaction and value, which in turn encourages BPJS Kesehatan participants' intention to revisit. Mitra Siaga Tegal Hospital management needs to adopt service strategies that are oriented towards customer satisfaction and value to build sustainable patient loyalty. Keywords: Customer Satisfaction, Customer Value, Service Quality, Revisit Intention